WANPRESTASI DALAM PERJANJIAN KREDIT PADA BANK RAKYAT INDONESIA (PT PERSERO)Tbk CABANG DENPASAR - Wijayanti Ekalandika, Mia; Westra, I Ketut; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum, 2013)
The titled of this papers is completion of default in credit agreement on Bank Rakyat Indonesia branch office at Denpasar. As for the writing of this papers uses empirical methods in order to develop knowledge within the banking and knowing the result of defaulting credit agreement. The Bank can do execution with debtor to sell collateral on the debtor's consent or otherwise, legal consequences arising debtor borrower defaults are required to pay for damages that have been awarded by the creditor; meet the agreement is accompanied by compensation payments.
Keywords: Default, Credit Agreement